A 11-year review of emergency obstetric hysterectomy (eoh) in Hospital Universiti Sains Malaysia Kubang Kerian, Kelantan January 2007 – December 2017 - Hashim, Noor Adibah Hanum Che (2020)
Introduction: Emergency obstetric hysterectomy (EOH) is one of the life saving procedure performed in cases of intractable hemorrhage due to uterine atony, rupture uterus and placental disorders and it is usually reserved for the situations where conservative measures fail to control the hemorrhage. It is sometimes associated with both maternal and perinatal morbidity and mortality. Objective: To evaluate the prevalence, indications, maternal and perinatal outcome associated with emergency obstetric hysterectomy in a tertiary care hospital. Methodology: A retrospective study conducted in the Department of Obstetric & Gynaecology in Hospital Universiti Sains Malaysia (HUSM) for 11 years from January 2007 until December 2017 involving a total of 43 women who underwent emergency obstetric hysterectomy. The records of all cases of emergency obstetric hysterectomy were analyzed included patient profile, obstetric history, details of present labour, indications for obstetric hysterectomy and the fetomaternal morbidity and mortality associated with emergency obstetric hysterectomy. Results: Among 79,777 deliveries, there were 43 cases of emergency obstetric hysterectomy, giving the prevalence of emergency obstetric hysterectomy was 0.29 per 1000 deliveries. Maternal demographic characteristics showed that mean age was 36 years old in caesarean hysterectomy group while mean age for postpartum hysterectomy group was 33 years old. The most common parity group encountered in emergency obstetric hysterectomy was para two to para five. Whether or not women underwent prior uterine surgery was investigated and 30 women (69.77%) had history of previous caesarean section. Of the 30 women with an obstetric history of caesarean delivery, 15 (50%) had more than two caesarean deliveries. Placenta accreta was the most common indication for emergency obstetric hysterectomy (30 women, 69.8%) followed by uterine atony (10 women, 23.3%), uterine rupture (2 women, 4.7%) and extended tear (1 woman, 2.3%). Futhermore, about 93.33% (28 out of 30 patients) with adherent placenta had history of caesarean section prior. No maternal mortality reported in this study. The most significant maternal complications postoperatively include coagulopathy (12 out of 43 women), where 27.91% required massive transfusion protocol, followed with re-laparotomy (4 women, 9.3%), and febrile illness (3 women, 6.98%). Most of the babies were born with good Apgar score. The perinatal complication include perinatal death, 2 out of 43 babies, 4.65% were fresh stillbirth were both cases were referred to our center for abruptio placenta. Conclusions: Caesarean section, especially repeat caesarean sections in women with placenta previa and uterine atony, significantly increased the risks of emergency obstetric hysterectomy. Emergency obstetric hysterectomy is safe with reduce complications compared to before with advancement of obstetric care and good clinical practice. Early decision to perform emergency obstetric hysterectomy is essential before the patient’s condition deteriorates